A new species of the worm-eel genus Neenchelys (Anguilliformes: Ophichthidae) from southern Taiwan - Ho, H.C.; Loh, K.H. (2015)
A new ophichthid worm-eel, Neenchelys gracilis sp. nov., is described from a specimen collected from southwestern Taiwan. It differs from its congeners by having: a minute pectoral fin, many filamentous cirri on the anterior nostril rim; a very slender body; a very small gill opening; and a vertebral formula of 30-78-200.